Papel do magnésio na prevenção e reversão de distúrbios motores experimentalmente induzidos - Kronbauer, Maikel (2014)
Chronic treatment of psychotic disorders is associated with adverse effects that affect motor function. Movement disorders include Parkinsonism, akathisia, dystonia and tardive dyskinesia. Magnesium (Mg) is an essential mineral for various physiological functions in the body and its supplementation is used in several diseases. The purpose of this study was investigate the effect of Mg supplementation on the prevention and reversal of orofacial dyskinesia (OD), designated as experiment 1 and 2, respectively, as well as the effect on oxidative stress parameters. In both experiments, male Wistar adult rats were used. In experiment 1, rats were randomly divided into two groups both supplemented with oral solution of magnesium aspartate (40 mg/Kg/mL) or deionized water. After 28 days of supplementation, half of each experimental group was treated with a reserpine solution (0.7 mg/kg/ml, sc) (Mg + R and R groups) or vehicle (C and Mg groups) for 3 days (every other day). One day (24 hours) after the last administration of R/vehicle, all animals were subjected to OD and catalepsy time behavioral assessments. In the experiment 2 rats were randomly divided into two groups and treated with a solution of reserpine (0.7 mg / kg / ml, sc) (R groups) or vehicle (Group C) for 3 days (every other day). Twenty-four hours after the last administration of R/vehicle, the development of OD was quantified. One-half of each experimental group was supplemented immediately once a day (by gavage) with magnesium aspartate (40 mg / kg / ml) (Mg, and groups R + Mg) or deionized water (groups C and R). The OD was measured during subsequent days (every 48 hours). Mg supplementation was maintained throughout the time of behavioral assessment (10 consecutive days). After behavioral evaluations, all animals were euthanized by exsanguination. Blood was drawn for analysis of erythrocytes lipid peroxidation (LP). The brains were immediately dissected for separating cortex, striatum and substantia nigra for determining reactive species (RS) and protein carbonyl (PC). The results showed that Mg supplementation before reserpine administration was sufficient to prevent movement disorder observed in the vacuous chewing movement frequency (VCM) and catalepsy time and also was able to prevent the generation of RS and PC, in both the cortex and the substantia nigra regions, also preventing LP in the erythrocytes. Supplementation of Mg after treatment with reserpine was able to minimize the frequency of VCM and catalepsy time, reduce the generation of RS and PC levels in both cortex and the corpus striatum regions and also reversing the increasing the level of LP in the erythrocytes. Our results underscore the importance of including alternative therapies through supplementation of essential natural substances, like magnesium, which can prevent or ameliorate motor disturbances, often related to chronic treatment of psychotic disorders that so far have no effective treatment.